Optical and Structural Characterization of Cu-Doped Ga2O3 Nanostructures Synthesized via Hydrothermal Method - Jiwoo Kim; Heejoong Ryou; Janghun Lee; Sunjae Kim; Wan Sik Hwang (Inorganics)
In this study, we investigate the optical and structural properties of Cu-doped β-Ga2O3 nanostructures synthesized via a hydrothermal method, followed by annealing in ambient O2. Different Cu doping concentrations (0, 1.6, and 4.8 at.%) are introduced to examine their effects on the crystal structure, chemical state, and optical bandgap of β-Ga2O3. X-ray diffraction (XRD) analysis reveals that the host β-Ga2O3 crystal structure is preserved at lower doping levels, whereas secondary phases (Ga2CuO4) appear at higher doping concentrations (4.8 at.%). X-ray photoelectron spectroscopy (XPS) confirms the presence of Cu2+ ions in both lattice substitution sites and surface-adsorbed hydroxylated species (Cu(OH)2). The optical bandgap of β-Ga2O3 is found to decrease with increasing Cu concentration, likely due to the formation of localized states or secondary phases. These findings demonstrate the tunability of the optical properties of β-Ga2O3 via Cu doping, providing insights into the incorporation mechanisms and their impact on structural and electronic properties.